PENGARUH KINERJA KEUANGAN, CORPORATE SOCIAL RESPONSIBILITY DAN GOOD CORPORATE GOVERNANCE TERHADAP RETURN SAHAM (Pada Perusahaan Indeks LQ45 yang terdaftar di Bursa Efek Indonesia Periode Tahun 2012-2015) - B31112057, Vina Amelia Eka Waty (Jurnal Manajemen Update, 2016)
This research is an empirical study annount to analyze the influence of financial performance using a proxy for Return On Assets (ROA), Corporate Social Responsibility / CSR, Good Corporate Governance proxy using the commissioners and board of directors to Return stock in the annual report.Â Â  The population used in this study is 45 companies included in the index LQ 45 listed in the Indonesia Stock Exchange ( BEI ) during the period 2012-2015. Based on purposive sampling method, obtained 96 samples of data samples from 24 companies. Hypothesis testing using multiple regression. The results of this study indicate that the Return On Aseets( ROA) and the Board of Directors have a significant effect on Return Equity, Corporate Social Responsibility / CSR, the Board of Commissioners did not affect the Stock Return Keywords : Return On Asstes ( ROA ), Corporate Social Responsibility, the Board of Commissioners, Board of Directors, Stock Return , LQ45